Reduction Behavior of Tin-containing phase in Tin-bearing Iron Concentrates under CO-CO2 Mixed Gases - Yu, yong; Li, hong-juan; Li, lei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The main purpose of this study was to ascertain the reduction behaviors of tin phase (SnO2) in tin-bearing iron concentrates at respective temperature of 1273 and 1373 K in diverse CO-CO2 mixed gases using chemical analysis, XRD and SEM-EDS analysis. The results show that the reduction behavior of SnO2 depends on the roasting temperature and CO content. At 1273 K, the SnO2 will be reduced to Sn (l) with the CO content being higher than 17.26 vol%, and there is no formtion of SnO(s). With the temperature increased to 1313 K, the SnO2 is reduced stepwisely in the order of SnO2 → SnO (l) → Sn(l) with CO content over 15.25 vol%. The kinetic study shows that activation energy of the reaction SnO2(s)+CO(g)=Sn(l)+ CO2(g) is 127.42 kJ/mol at 1073-1173 K, being far lower than that in the reduction of SnO2(s) into SnO(g) at 1273-1323 K, which leads to a conclusion that the tin in tin-bearing iron concentrates could be removed effectively after the Sn(l) sulfurated into SnS at relatively lower temperatures (1073-1173 K) using the sulfidation roasting method.